One-pot two-step perfluoroalkylsilane functionalization of multi-walled carbon nanotubes for polyurethane-based composites. (3rd May 2017) - Li, Shasha; Du, Xiao; Hou, Caiying; Hao, Xiaogang; Jia, Jinlan; Guan, Taotao; Yi, Tingfa; Ma, Guozhang
Abstract: A facile approach has been developed to prepare perfluoroalkylsilane functionalized multi-walled carbon nanotubes (MWCNTs) with high grafting content through one-pot two-step reactions. In this process, hydroxyl derivatized MWCNTs (hydroxylized MWCNTs) were covalently functionalized with 3-aminopropyl triethoxysilane by silanisation reaction, and subsequently reacted with hexafluorobutyl acrylate or dodecafluoroheptyl acrylate by Micheal-addition reaction. SEM, FT-IR and TGA characterizations demonstrated that the perfluoroalkylsilane were covalently attached onto the surface of MWCNTs and the higher molecular weight of perfluoroalky acrylate yielded higher grafting content. The perfluoroalkylsilane functionalized MWCNTs showed improved dispersibility and strong interfacial adhesion in/with polyurethane matrix. An increase in the grafting content led to a decrease the crystallinity and hydrogen bonding in the PU composites. As a result, the composites showed increased elongation and unimproved tensile strength, but reduced storage modulus and loss factor. Meanwhile, the higher grafting content offered their composite with higher hydrophobicity, lower percolation threshold and more enhanced electronic conductivity. Graphical abstract: Highlights: Functionalization of MWCNTs by silanisation and Micheal-addition reactions in one-pot. The high molecular weight of perfluoroalky acrylate yields high grafting content. MWCNTs/PU composites with high surface hydrophobicity, low percolation threshold and high strain.